2021
DOI: 10.3201/eid2708.204969
|View full text |Cite
|
Sign up to set email alerts
|

Highly Pathogenic Avian Influenza A(H5N8) Virus Clade 2.3.4.4b, Western Siberia, Russia, 2020

Abstract: She is currently the secretary of the Food-and Water-borne Infections Study Group from the European Society of Clinical Microbiology and Infectious Diseases. Her main research interests are in the molecular epidemiology, genomics, and evolution of antimicrobial-resistant Enterococcus. References 1. Davies RH, Lawes JR, Wales AD. Raw diets for dogs and cats: a review, with particular reference to microbiological hazards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…Thus, it is possible that the H5N2 and H5N8 HPAIVs identified in the present study emerged through reassortment events in this area. The detection of H5 HPAIVs of the G2 cluster in poultry in Russia (Lewis et al., 2021; Sobolev et al., 2021) and in wild birds in the present study highlights the importance of understanding the extent of genetic variation among AIVs in Siberia for forecasting outbreaks in East Asia and Western Europe.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Thus, it is possible that the H5N2 and H5N8 HPAIVs identified in the present study emerged through reassortment events in this area. The detection of H5 HPAIVs of the G2 cluster in poultry in Russia (Lewis et al., 2021; Sobolev et al., 2021) and in wild birds in the present study highlights the importance of understanding the extent of genetic variation among AIVs in Siberia for forecasting outbreaks in East Asia and Western Europe.…”
Section: Discussionmentioning
confidence: 49%
“…Continuedthrough reassortment events in this area. The detection of H5 HPAIVs of the G2 cluster in poultry in Russia(Lewis et al, 2021;Sobolev et al, 2021) and in wild birds in the present study highlights the importance of understanding the extent of genetic variation among AIVs in Siberia for forecasting outbreaks in East Asia and Western Europe.Our phylogeographic analyses also indicated that the present avian influenza surveillance activities conducted in Siberia are helpful to evaluate the origin of viruses that have caused HPAI outbreaks in Europe and Asia. In the present study, some of the internal genes of Japanese H5N8 HPAIVs showing the E3, E5 and E7 genotypes were genetically closely related to those of AIVs circulating in Siberia.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…The viruses in subgroup A were derived from the ancestral strain of A/Turkey/Egypt/AI20285/2019 isolated in Egypt, North Africa, in 2019, while the viruses in subgroup B were from A/guinea fowl/Nigeria/OG-GF11T_19VIR8724-7 ( Figure 2 b,c). The ML phylogenetic trees of the other seven segments were also derived from the isolate from Egypt, suggesting that the H5N8 HPAIVs from common cranes were standard “Egyptian-like” ( Figure S1 ) [ 24 ]. These isolations might show a similar recombination pattern as Egyptian-like H5N8 HPAIVs, with HA, NA, M, and NS gene segments from the Russian HPAI H5N8 virus, and PB2, PB1, PA, and NP segments from the Eurasian H6N2, H5N6, and H1N1 virus [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic analysis of all eight genes revealed that the H5N8 AIVs in the study were clustered together with the H5N8 AIVs isolates of branch 2.3.4.4b from wild birds and poultry in Europe, Russia, Siberia, and China, during 2020–2022 with the common ancestor of A/Turkey/Egypt/AI20285/2019. These viruses presented as standard “Egyptian-like” genetic strains [ 24 ]. As an intersection of five global migration routes, including East Asia–Australia, Central Asia, the Black Sea–Mediterranean, West Asia–East Africa, and East Atlantic, Siberia plays a critical role as the breeding ground for wild wading birds from Europe, Africa, the Middle East, Central Asia, and Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%